1985
DOI: 10.1289/ehp.8562197
|View full text |Cite
|
Sign up to set email alerts
|

Study of DNA methylation by tobacco-specific N-nitrosamines.

Abstract: An enzyme-linked immunosorbent assay (BA-ELISA) involving use of biotin-labeled anti-rabbit IgG and avidin-labeled horseradish peroxidase was developed for the measurement of 06-methyl-2'-deoxyguanosine (06-MedGuo). Up to 5 jg of methylated DNA was enzymatically hydrolyzed, and the extent of inhibition of binding of immobilized 06-MedGuo-bovine serum albumin to rabbit anti-O6-MedGuo was measured. Fifty percent inhibition of antigen-antibody binding was achieved with 2.5 pmole of of 06-MedGuo. Separation of 0-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…They are present in the respiratory and olfactory parts of the nasal mucosa, with the respiratory mucosa levels being higher. Consistent with expectations, O 6 -mG is not detected in nasal mucosa or liver of rats treated with NNN (178).…”
Section: In Vivo Metabolism Of Nnnsupporting
confidence: 90%
See 1 more Smart Citation
“…They are present in the respiratory and olfactory parts of the nasal mucosa, with the respiratory mucosa levels being higher. Consistent with expectations, O 6 -mG is not detected in nasal mucosa or liver of rats treated with NNN (178).…”
Section: In Vivo Metabolism Of Nnnsupporting
confidence: 90%
“…Other adducts are probably also produced, based on studies of other methylating nitrosamines and nitrosoureas, but these have not been identified from NNK (190). The first studies quantified O 6 -mdG in cultured rat nasal mucosa treated with NNK or NNAL; relatively high levels were detected by HPLCimmunoassay, consistent with the high activity in the nasal mucosa for R-hydroxylation of NNK (177,178). DNA methylation by NNK is observed in a number of in vitro studies with different systems capable of its metabolic activation, including rat lung cells and lung, liver, or nasal mucosal microsomes (with added DNA), rat oral tissue, and hamster lung (50,71,78,91).…”
Section: Dna Methylation (R-methylene Hydroxylation)mentioning
confidence: 68%
“…Aberrant hypermethylation of genomic DNAs and increased levels of DNA methyltransferase (DNA MeTase) activity have been detected in NNK and Cd treated cells [22,23,96]. Furthermore, both NNK and Cd also suppressed histone H3 acetylation at the LO core promoter region (Figure 4C).…”
Section: Lo As a Target Of Cs At Multiple Molecular Levelsmentioning
confidence: 95%
“…Metabolic activation of NNK by cytochrome P-450 (CYP) is required to exert its carcinogenic activity [21]. Although it is established that NNK damages DNA via formation of methyl adducts [22,23] and mutation of p53, a tumor suppressor gene [24], the intracellular events elicited by CS/NNK and their underlying pathological mechanisms leading to cell injury and cancer development remain unclear.…”
Section: Major Pathogenic Agents Of Csmentioning
confidence: 99%
“…The diazohydroxides formed are the methylating methanediazohydroxide or the pyridyl (oxo or hydroxy) butylating 4-(3-pyridyl)-4-(oxo or hydroxy)-1-butanediazohydroxide (6,12). The formation of methanediazohydroxide and its corresponding diazonium ion has been inferred from demonstration of methylations at different sites in DNA; N7- methylguanine, O 6 -methylguanine, and O 4 -methylthymine were observed (13)(14)(15)(16). The first study on pyridyloxobutylating species showed the presence of radioactivity in DNA from rats treated with [2′- 14 C]NNN (metabolized to the pyridyloxobutylating species only) but did not demonstrate covalent binding and adduct structure (13).…”
Section: Introductionmentioning
confidence: 99%